Mannose Receptor Mediates the Activation of Chitooligosaccharides on Blunt Snout Bream (Megalobrama amblycephala) Macrophages - Ouyang, Aotian; Wang, Huabing; Su, Jianguo; Liu, Xiaoling (Frontiers in Immunology, 2021)
Chitooligosaccharide (COS) is an important immune enhancer and has been proven to have a variety of biological activities. Our previous research has established an M1 polarization mode by COS in blunt snout bream (Megalobrama amblycephala) macrophages, but the mechanism of COS activation of blunt snout bream macrophages remains unclear. In this study, we further explored the internalization mechanism and signal transduction pathway of COS6 in blunt snout bream macrophages. The results showed that mannose receptor C-type lectin-like domain 4-8 of M. amblycephala (MaMR CTLD4-8) could recognize and bind to COS6, and mediate COS6 into macrophages by both the clathrin-dependent and caveolin-dependent pathways. In the inflammatory response of macrophages activated by COS6, the expression of TNF-α, IL-1β, and NOS2 was significantly inhibited after MaMR CTLD4-8 specific antibody blockage. However, even it was blocked, the expression of these inflammatory factors was still relatively up-regulated, which suggested that there are other receptors involved in immune regulation. Further studies indicated that MaMR CTLD4-8 and Toll like receptor 4 (TLR4) cooperated to regulate the pro-inflammatory response of macrophage caused by COS6. Taken together, these results revealed that MR CTLD4-8 is indispensable in the process of recognition, binding, internalization and immunoregulation of COS in macrophages of blunt snout bream.